Chemical and sensory characteristics of Italian virgin olive oils from Grossa di Gerace cv. Issue 2 (19th May 2015) - Di Serio, Maria Gabriella; Di Giacinto, Luciana; Di Loreto, Giuseppina; Giansante, Lucia; Pellegrino, Massimiliano; Vito, Raffaella; Perri, Enzo
Abstract : The aim of this study was to provide an additional element of knowledge and evaluation on extra virgin olive oil from the Italian region Calabria, belonging to the Grossa di Gerace cv. Then, the following chemical, physical–chemical, and sensory analyses have been performed: free acidity, peroxide value, UV spectrophotometric indices, ethyl esters, waxes, tocopherols, fatty acids, triglycerides, sterols, alcohols, phenolic substances, dynamic headspace volatile compounds, and sensory profile. The analytical investigation allowed us to highlight the great potential of this cultivar: a "quality" product that will satisfy consumer expectations for a particular food, and especially a "typicality" because of its unique attributes in the zone of production. According to the results provided by the analysis carried out on the extra virgin olive oil samples from "Grossa di Gerace" and its mixtures with another important cultivar of Calabria, "Carolea, " and thanks to statistical tools, 17 variables have been identified that could be considered markers of single cultivar olive oils of "Grossa di Gerace": phytol, palmitic acid, 1‐hexanol, trans ‐2‐hexen‐1‐ol, α‐amyrin, 3, 4‐DHPEA‐EA‐H, palmitoleic acid, apigenin, methyl‐luteolin, geranylgeraniol, 3, 4‐DHPEA‐EA, OOL + LnPP, PoOO, PoOP + SPoL + SOLn + SPoPo, citrostadienol, luteolin, and trans ‐2‐hexenal. The Principal Components Analysis (PCA) applied to the 17 variables has permitted us to distinguish blends with more than 10% of "Carolea." Practical applications: The study carried out on single cultivar extra virgin olive oil of Grossa di Gerace has been executed for several practical applications: (i) the knowledge of the chemical profile of the oil is useful to define the sensory, nutritional, and conservative quality of this product; (ii) the identification of analytical parameters is useful for a Protected Denomination of Origin (PDO) characterization; (iii) to protect the single cultivar extra virgin olive oil, inserted into the ATP, from mixtures with other oils, by the identified analytical markers. According to the results provided by the analysis carried out on the extra virgin olive oil samples from "Grossa di Gerace" and its mixtures with another important cultivar of Calabria, "Carolea, " and thanks to statistical tools, 17 variables have been identified that could be considered markers of single cultivar olive oils of "Grossa di Gerace." The Principal Components Analysis applied to the 17 variables has permitted us to distinguish blends with more than 10% of "Carolea." Abstract : According to the results provided by the analysis carried out on the extra virgin olive oil samples from "Grossa di Gerace" and its mixtures with another important cultivar of Calabria, "Carolea, " and thanks to statistical tools, 17 variables have been identified that could be considered markers of single cultivar olive oils of "Grossa di Gerace." The Principal Components Analysis applied to the 17 variables has permitted us to distinguish blends with more than 10% of "Carolea."